Numerical simulation study on the effect of spindle-shaped louver fins on heat transfer performance of wasp-waisted tube radiator - Zongpeng Ma; Ying Huang; Jiangnan Song; Xiang Zhang; Tong Gao; Lunjun Chen (Case Studies in Thermal Engineering, 2023)
The shape of louver fins has the significant influence on the radiator performance. Based on the existing radiator with wasp-waisted tube type, this research changes the end shape of traditional rectangular louver fin, develops a new type of spindle-shaped louver fin (SSLF), and studies the influence of spindle end angle of new louver fin on the air side heat transfer and resistance performance in the range of Reynolds number 500–3500 by numerical simulation. The research shows that the spindle design at the end of the new louver fin effectively reduces the pressure loss of air at the end and forms a low-speed zone near the wall of the fin when air flows through the fin, which improves the convection heat exchange efficiency between the fin and air. When the Reynolds number is 3500, the pressure drops of SSLF1#, SSLF2# and SSLF3# at different angles are 27.63%, 21.31% and 12.43% lower than those of traditional louver fins, respectively. The convection heat transfer coefficient increased by 0.84%, 5.33% and 2.69% respectively. At Reynolds number 500–2300, the PEC value of SSLF2 # is the highest, reaching 1.179. At Reynolds number 2300–3500, the PEC value of SSLF1 # is the highest, reaching 1.123.